Diagnosis of fetal growth restriction in perinatal deaths using brain to liver weight ratios. Issue 1 (January 2015) - Stephens, Alexandre S.; Bentley, Jason P.; Taylor, Lee K.; Arbuckle, Susan M.
<x xml:space="preserve">Abstract</x> Summary We determined brain to liver weight ratio (BLWR) thresholds for fetal growth restriction (FGR) using autopsy information on 395 perinatal deaths comprising stillborn babies who died during labour and neonatal deaths. FGR was defined using two methods: (1) birth weight for gestational age (WGA) less than the 10th percentile; and (2) WGA less than the 10th percentile or discordant birth weight/length. The association between BLWR and FGR was investigated using odds ratios, and classification statistics were calculated for a range of BLWR thresholds. Using WGA, 84 cases (21.3%) were FGR and a further 15 cases (n = 99, 25%) had discordant birth weight/length. The BLWR ranged from 1.02 to 7.30 and was positively associated with FGR. BLWR was not associated with FGR for babies with congenital central nervous system or chromosomal abnormalities. Excluding these, for FGR defined using WGA and discordant birth weight/length, a BLWR threshold of 5.0 was 100% predictive of FGR. A BLWR threshold of 3.0 for babies over 28 weeks gestation and 3.7 for more preterm babies optimised case detection while minimising missed and false positive cases. Additional evidence of FGR should be sought for babies with a BLWR of less than 5.0 to confirm FGR.